On the exact solutions of the fractional (2+1)- dimensional Davey - Stewartson equation system - Gülnur Yel (An International Journal of Optimization and Control: Theories & Applications, 2017)
In this work, we construct the exact traveling wave solutions of the fractional (2+1)-dimensional Davey-Stewartson equation system (D-S) that is complex equation system using the Modified Trial Equation Method (MTEM). We obtained trigonometric function solutions by this method that are new in literature.